2021
DOI: 10.1371/journal.pone.0261444
|View full text |Cite
|
Sign up to set email alerts
|

Migratory wild birds carrying multidrug-resistant Escherichia coli as potential transmitters of antimicrobial resistance in China

Abstract: Migratory birds play an important role in the spread of multidrug-resistant (MDR) bacteria. To investigate the prevalence of MDR Escherichia coli in migratory birds in China and potential relationships with the environment, a total of 1387 samples (fecal samples, cloacal swabs, or throat swabs) were collected from migratory birds from three different river basins in China. The collected samples were processed and subjected to bacteriological examinations. Antimicrobial susceptibility testing of the recovered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
2
31
2
Order By: Relevance
“… Ben Yahia et al (2020) reported the first evidence of ESBL-producing E. coli with the blaCTX-M-15 genes in the wildlife of Tunisia and Africa. Yuan et al (2021) also demonstrated role of migratory birds in disseminating MDR genes. Our study indicates that birds containing pathogenic and antibiotic-resistant genes may disperse them to the new locality and cause infection in other birds, farm animals, and humans.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… Ben Yahia et al (2020) reported the first evidence of ESBL-producing E. coli with the blaCTX-M-15 genes in the wildlife of Tunisia and Africa. Yuan et al (2021) also demonstrated role of migratory birds in disseminating MDR genes. Our study indicates that birds containing pathogenic and antibiotic-resistant genes may disperse them to the new locality and cause infection in other birds, farm animals, and humans.…”
Section: Discussionmentioning
confidence: 94%
“…E. fergusonii has been a cause of spleen and liver infection in calf and chicken ( Beli and Duraku, 2017 ), non-human primates ( Glover et al, 2017 ) and cattle pneumonia ( Rimoldi and Moeller, 2013 ). Several investigations demonstrate that wild birds uptake the pathogenic bacteria from wastes and shed them into new locality which results in broad-range outbreaks as well as endemic spreads of multidrug-resistant strains ( Sharif et al, 2020 , Yuan et al, 2021 ). The plasmid contains resistant genes that may transfer horizontally to completely different microorganisms and bring structural changes ( Dolejska and Papagiannitsis, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to understand that some wild animals with acquired resistance genes can migrate from human-impacted areas to pristine environments and spread the resistance genes. MDR E. coli isolates were detected in migratory birds in both northern and southern China, but the rate of resistance was higher in the south [ 124 ], which confirms the role of the environment in the spread of AR. Animal migration may interfere with our understanding of the origin of AR in pristine environments because the sources of resistant bacteria carried by migratory animals are usually unknown.…”
Section: Vehicles/pathways For Antimicrobial Resistancementioning
confidence: 96%
“…Resistance phenotypes may be transferred from wild birds and mammals to food-producing animals that share the same environment with the wildlife [ 122 ]. Wild animals may spread AR in surface waters through their feces and swimming [ 124 ]. Humans may be infected with zoonotic antimicrobial-resistant pathogens through their interactions with wild animals and their habitats or by killing the animals for food.…”
Section: Vehicles/pathways For Antimicrobial Resistancementioning
confidence: 99%
“…Although antibiotics and antimicrobial resistance are known to occur naturally in the environment [ 16 , 20 , 21 ], different anthropogenic sources have been identified as additional sources of environmental contamination [ 22 , 23 , 24 , 25 , 26 ]. Wildlife most probably acquires antimicrobial-resistant bacteria from environmental sources [ 11 , 27 , 28 ], and can also act as a reservoir and vector for infection or colonisation [ 15 , 29 , 30 , 31 ]. In this context, individual wildlife species could be used as effective bioindicators to display the level of environmental contamination as well as the potential of a public health risk caused by antimicrobial-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%